2019
DOI: 10.1080/14786419.2019.1678614
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of squalene synthase of rat liver by abietane diterpenes derivatives

Abstract: In the current study, chemical composition of cultivated Salvia canariensis L was determined. In this work, carnosol was the main product isolated, and the concentration of rosmanol is also significant. We prepared more lipophilic derivatives from carnosol, and both isolated and semisynthetic abietane diterpenes were evaluated in vitro as inhibitors of squalene synthase isolated from rat liver.Among the compounds tested, carnosol was the most potent inhibitor with an IC 50 value of 17.6 μM. These results highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The plant parts were sterilized before planting using ethyl alcohol at a concentration of 70% for 1 minute. Then the plant parts were sterilized with sodium hypochlorite following the experimental design with three concentrations (4,8,12) % and at intervals of 15-20 minutes, and the best result was using an 8% concentration for 15 minutes, which gave the lowest percentage of contamination. After the sterilization, the plant parts were washed by sterile distilled water 3 times for 5 minutes in in laminar flow.…”
Section: Preparation and Sterilization Of Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant parts were sterilized before planting using ethyl alcohol at a concentration of 70% for 1 minute. Then the plant parts were sterilized with sodium hypochlorite following the experimental design with three concentrations (4,8,12) % and at intervals of 15-20 minutes, and the best result was using an 8% concentration for 15 minutes, which gave the lowest percentage of contamination. After the sterilization, the plant parts were washed by sterile distilled water 3 times for 5 minutes in in laminar flow.…”
Section: Preparation and Sterilization Of Explantsmentioning
confidence: 99%
“…Its medical importance is due to the fact that it contains essential oil, as the chemical composition of these secondary metabolites varies with different environmental conditions [11]. Recent studies have shown that plant extracts are an effective inhibitor of food pathogens [12]. Its biological properties are due to its high content of secondary metabolism such as carnosic acid, carnosol, rosmanol, rosmarinic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main diterpenoid carnosol ( 19 ) was obtained from the acetone extract of Salvia canariensis by Alonso and his group to follow the protocol designed by Marrero et al [25] The design and semisynthesis were started from natural diterpenoid ( 19 ) to enhance the lipophilicity of semisynthetic derivatives through the chemical transformations of the hydroxyl group of carnosol ( 19 ) in 2019 [26] . The parent compound ( 19 ) in CH 2 Cl 2 undergoes the acetylation reaction in the presence of the acetic anhydride (Ac 2 O), DMAP, and triethanolamine (TEA) to afford ester ( 20 ) at room temperature in 92.5 % yield.…”
Section: Semisynthesis At Room Temperature and Pharmacological Aspectsmentioning
confidence: 99%
“…Rosmarinus officinalis L. is a medicinal plant used since ancient times, whose biological properties are attributable to its high content in phytochemicals as carnosol, carnosic acid, rosmarinic acid, rosmanol or ursolic acid, among others [ 4 ]. Of particular interests are carnosic acid and its oxidized derivatives, exhibiting various interesting biological activities [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%